2014
DOI: 10.5935/0004-2749.20140003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of subconjunctival bevacizumab for recurrent pterygium

Abstract: Purpose: To evaluate the clinical outcome(s) and complication(s) of subcon junctival bevacizumab treatment in patients with recurrent pterygium. Methods: This prospective case series included patients who had undergone pterygium surgery and were diagnosed with recurrent pterygium. All patients received one subconjunctival injection of 0.5 mL of bevacizumab (2.5 mg/0.1 mL). The main outcome was the change in size and clinical appearance. The clinical appearance of the pterygium was graded according to Tan and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…Stival et al. () similarly reported significant decreases in pterygium grading, size and mean surface area. The majority of patients’ symptoms also improved.…”
Section: Resultsmentioning
confidence: 91%
“…Stival et al. () similarly reported significant decreases in pterygium grading, size and mean surface area. The majority of patients’ symptoms also improved.…”
Section: Resultsmentioning
confidence: 91%
“…It has been reported that the single postoperative administration of subconjunctival bevacizumab is well tolerated and decreases the number and caliber of corneal blood vessels. 189 Nevertheless, this favorable effect is incomplete and temporary. Other researchers have reported a decrease in the frequency of fibrovascular tissue after bevacizumab treatment, with no statistically significant differences in levels between the treated and non-treated groups.…”
Section: Treatmentmentioning
confidence: 98%
“…Однако в развитых странах наиболее частой причиной развития слепоты является офтальмогерпес, вызванный Herpes simplex virus (HSV) [10,29,30], и, реже, herpes zoster. Кератит, вызванный вирусом простого герпесаэто иммуноопосредованное заболевание, которое редко возникает при первичном инфицировании.…”
Section: заболевания роговицы сопровождаемые патологическим ангиогенunclassified
“…Распространение птеригиума в оптическую зону может угрожать зрению и требует хирургического лечения. Рецидивирующий характер течения заболевания и повторные операции могут приводить к истончению роговицы, астигматизму [29,30].…”
Section: заболевания роговицы сопровождаемые патологическим ангиогенunclassified